Principles of Electronic Prescribing - Goundrey-Smith, Stephen (Health Informatics,, 2008)
Electronic prescribing (EP) is a complex discipline, the success of which relies on the successful interplay of system design, data support and clinical practice. It represents the use of electronic systems to facilitate and enhance communication of a prescription or medicine order, and improves legibility and completeness of prescriptions, improves availability of electronic decision support tools at the point of prescribing, enables a comprehensive audit trail, and reduces medication-related errors. These benefits are far-reaching in significance, both in terms of their effects on risk management and risk reduction and their financial impact. Given the likely growth of interest in electronic medicines management, this discussion of relevant design issues and their impact is timely. Electronic Prescribing: Principles and Practice discusses the basic principles of the design and implementation of secondary care electronic medicine management systems, and how they impact hospital workflow and clinical practice. It documents the key aspects of EP systems for use in secondary care, including design issues, data support, benefits and the ways in which electronic medicines management systems can optimize clinical and professional practice.Because of the significance of electronic medicines management to the whole medical supply chain, and the various stakeholders involved in the IT implementations, the book will be of interest to a wide range of professionals, from hospital pharmacists and prescribing physicians to health system managers and informaticians.